SOCIAL MEDIA USE AND ANXIETY IN ADOLESCENTS: MECHANISMS, CONTEXT, AND DIGITAL INTERVENTIONS — A NARRATIVE REVIEW - Kubicz-Mzabi, Sabina; Ignarska, Justyna; Piech, Bartosz; Judzińska, Alicja; Sobczyńska, Kamila; Terbosh, Magda; Trojanowska, Emilia; Dubaj, Magdalena; Kwolek, Marlena; Osipowska, Julia (International Journal of Innovative Technologies in Social Science, 2026)
The widespread use of social media among adolescents has drawn increasing attention to its potential impact on mental health, particularly anxiety. However, existing findings are heterogeneous and sometimes difficult to interpret due to differences in study design and measurement approaches. The aim of this narrative review was to synthesize current evidence on the relationship between social media use and anxiety in adolescents, with a focus on patterns of use, underlying mechanisms, contextual factors, and digital interventions.A literature search was conducted across major peer-reviewed databases, including PubMed, ScienceDirect, and other relevant sources. Studies were included if they examined social media use in relation to anxiety or related mental health outcomes in adolescent populations. Both empirical studies and review articles were considered.Overall, available evidence suggests that social media use is associated with anxiety symptoms, although the strength of this relationship is generally modest and varies across studies. The impact of social media appears to depend less on time spent online and more on patterns of engagement and individual vulnerability. Multiple mechanisms, including social comparison, fear of missing out, sleep disruption, and exposure to negative online experiences, have been proposed to help explain these associations. The relationship also appears to be bidirectional, with adolescents experiencing anxiety potentially engaging differently with social media.Digital interventions, particularly internet-delivered cognitive behavioral therapy, show promise in reducing anxiety symptoms, although their effectiveness varies depending on user engagement and level of guidance. Current evidence suggests that social media is neither inherently harmful nor universally beneficial, and its impact appears to depend on how, why, and in what context it is used. Further research using longitudinal designs and improved measurement approaches is needed to better understand these relationships.